Studi Hadīṡ: Pemikiran dan Kontribusi KH. Ahmad Luthfi Fathullah - Aswan, Dimas Zairul (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
especially in Indonesia, most researchers engaged in studies in the field of ḥadīṡ said that it is very likely that ḥadīṡ began to enter Indonesia around the 17th to 18th centuries. This research aims to determine the thoughts and contributions of Ahmad Luthfi Fathullah in the study of ḥadīṡ. The problem in this research is how Ahmad Luthfi Fathullah thought in the field of ḥadīṡ Nabī and what contributions Ahmad Luthfi Fathullah made to the study of ḥadīṡ. This research uses a qualitative approach, with data collection techniques through interviews, observation and document study. The results of this research found that Ahmad Luthfi Fathullah had very good thoughts in the study of ḥadīṡ. In the results of his thoughts, he felt that in Indonesia there was still very little ḥadīṡ literature, so starting from this problem, Ahmad Luthfi Fathullah published a digitization of ḥadīṡ to make it easier for people to find references around ḥadīṡ Rasūlullāh. In Rasūlullāh's thoughts on understanding ḥadīṡ, according to Ahmad Luthfi Fathullah, if a ḥadīṡ cannot be understood textually, then to get a correct understanding the ḥadīṡ must be understood textually.